Enhancing Quality of Early Childhood Education in Nigeria Through Adoption of Blended Learning By Early Childhood Educators - Lawal, Oluwaseun Temitope; Oladunni Gbenga-akanmu, Taiwo; Akinyemi Amoo, Tesleem (The University of Kuningan, 2023)
ABSTRACTIt has been observed in the recent that the reality and influence of Blended Learning on achieving quality education across the globe cannot be under estimated. This has made it a necessity for all educators to adopt blended learning as a teaching strategy. The study investigated the adoption of blended learning by Early Childhood Education teachers in Nigerian Primary Schools. Descriptive survey design was employed for the study. The sample size consisted of 450 teachers that were randomly selected from the three Senatorial Districts in Ondo State Nigeria. A self-designed instrument was used to collect data for the study. The instrument was validated and tested for reliability at coefficient of 0.75. Data collected were analysed using frequency, percentages and ranking. The result revealed that 387(86%) of the teachers in Ondo state has adopted blended learning and majority of the teachers had positive perceptions of BL as a teaching strategy. It was concluded that ECE teachers in Ondo state Nigeria has adopted blended learning as a teaching strategy. The study recommended that government and other stakeholders should give more awareness on BL and provide teachers and learners with necessary facilities needed in school and home.Keywords: blended learning; early childhood education; primary school; teacher; teaching strategy